Schillers Moralästhetik als verfehlte Kant-Kritik und die ›Kalokagathia‹-Idee: - Neymeyr, Barbara (Verlag Karl Alber, 2023)
This book critically analyses Schiller's moral aesthetics as a supposedly more moderate alternative to Kant's ethics of duty. In a departure from common research theories, it shows that the objections of Schiller, Schopenhauer and Nietzsche to Kant are based on misjudgements and that Schiller's own draft even implies a form of moral rigorism against his will. Moreover, Schiller's conception of 'grace' and 'dignity' contains inconsistencies, the cause of which is explored in this study. Beyond the problem-oriented systematic analyses the book conducts, its cultural and historical horizon-building demonstrates how much Schiller and Hölderlin are influenced by the ancient ideals of 'kalokagathia' and 'sympatheia', which, however, are fundamentally different from Kant's philosophy.